Analisis Antropologi Sastra dalam Novel Tenggelamnya Kapal Van Der Wijck Karya Buya Hamka - Yohana Sianturi, Rut Cahaya; Nuraeni, Windry; Yunus, Syarifudin (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
The novel Tenggelamnya Kapal Van der Wijck by Hamka represents the social reality of Minangkabau society through a tragic love story full of cultural values ​​and social conflict. This study aims to analyze the aspects of literary anthropology in the novel, focusing on the representation of customs, social values, and the dynamics of individual relationships with society. The results of the analysis show that Hamka raises the issue of social inequality, oppression in the name of customs, and the struggle of individuals in facing the dominance of cultural structures. Through the characters of Zainuddin and Hayati, these novel expresses criticism of rigid customary values ​​that do not side with humanity. Literary anthropology in this novel plays an important role in connecting fictional narratives with social reality, as well as being a means of cultural reflection and collective identity of society. With a strong and emotional storytelling style, Hamka successfully voices the conflict between tradition and modernity, and invites readers to understand the complexity of culture in people's lives. This novel is not only a literary work, but also a cultural document that reflects the social dynamics of its time.